Minimally invasive treatment of Talar neck fractures using the calcaneal distractor - a technical note - M. Katzensteiner; M. Bischofreiter; G. Schalamon; R. Ortmaier; Ch. Rodemund; G. Mattiassich (Foot & Ankle Surgery: Techniques, Reports & Cases)
Talar neck fractures, though rare, pose significant challenges in treatment due to their complex nature and potential for severe complications. Despite the fact that most of talar fractures are treated operatively, there is scarcity of clear recommendations concerning appropriate surgical technique and care. Historically, conservative management was favored, but open reduction and internal fixation (ORIF) have become the standard of care. However, merely restoring rotation, axis, and length is insufficient; restoring the articulating surface in an anatomical manner is essential for long-term joint health. Surgical access to the fracture site via anteromedial and anterolateral approaches provides visualization, but risks compromising the sensitive, partly retrograde blood supply to the talar body. While being biomechanically superior, screws inserted from a posterior to anterior direction pose challenges in soft tissue preservation and accurate placement. Despite widespread usage of this technique, postoperative outcomes remain suboptimal with considerable rates of malunion, osteonecrosis and osteoarthritis. An overlooked technique in the literature is the use of a distractor, commonly employed in minimally-invasive surgical calcaneal fracture treatment in order to maintain length, alignment and joint reposition during fixation. With the potential to reduce soft tissue damage and preserve the blood supply minimally invasive techniques present a promising advancement in fracture management of talar neck fractures.